2018
DOI: 10.12659/msm.908714
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuates Pulmonary Inflammation in Lipopolysaccharide Induced Acute Lung Injury in Neonatal Rat Model by Activating Peroxisome Proliferator-Activated Receptor γ (PPARγ) Pathway

Abstract: BackgroundThis study aimed to investigate the therapeutic effect of curcumin in lipopolysaccharide (LPS) induced neonatal acute lung injury (ALI) and the possibly associated molecular mechanisms.Material/MethodsALI neonatal animal model was established by using LPS. Curcumin and/or peroxisome proliferator-activated receptor γ (PPARγ) inhibitor BADGE (bisphenol A diglycidyl ether) were administrated to animals. Lung edema was evaluated by PaO2 and lung wet/dry weight ratio (W/D) measurements. EMSA was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
1
28
0
2
Order By: Relevance
“…Mechanistically, curcumin protects the lung by inhibiting inflammation and production of ROS through regulation of multiple signaling pathways engaging peroxisome proliferatoractivated receptor γ (PPARγ) (Cheng et al, 2018), JNK (Xiao et al, 2019), NF-κB (Suresh et al, 2012;Wang et al, 2018), and Nrf2 (Dai et al, 2018;Han et al, 2018). Notably, the role of curcumin in regulating Nrf2/HO-1 has been reported in IAV infection (Dai et al, 2018;Han et al, 2018).…”
Section: Curcumin Alleviates Exudation and Edema Caused By Inflammationmentioning
confidence: 99%
“…Mechanistically, curcumin protects the lung by inhibiting inflammation and production of ROS through regulation of multiple signaling pathways engaging peroxisome proliferatoractivated receptor γ (PPARγ) (Cheng et al, 2018), JNK (Xiao et al, 2019), NF-κB (Suresh et al, 2012;Wang et al, 2018), and Nrf2 (Dai et al, 2018;Han et al, 2018). Notably, the role of curcumin in regulating Nrf2/HO-1 has been reported in IAV infection (Dai et al, 2018;Han et al, 2018).…”
Section: Curcumin Alleviates Exudation and Edema Caused By Inflammationmentioning
confidence: 99%
“…Curcumin is used as a spice in foods and for different purposes such as cosmetic and pharmaceutical industries in world (Hosseini & Hosseinzadeh, 2018). Curcumin has several pharmacological effects such as antioxidant, anticancer, antibacterial, antiviral, and antidiabetic effects (Fan et al., 2015; Moghadamtousi et al., 2014; Zhu et al., 2017), as well as anti‐inflammatory activity (Cheng, Yang, Hu, Zhu, & Liu, 2018). As the potential role of curcumin to treat many inflammatory disorders, at the first step we will describe all effects of curcumin that may be useful to treat COVID‐19, and then, we explain the possible molecular mechanisms of it.…”
Section: Covid‐19 and Current Drug Development Research Projectsmentioning
confidence: 99%
“…The aforementioned studies have revealed that miRNAs exert protective effects against lung injury via repressing inflammatory responses. Moreover, a number of studies have indicated that attenuating pulmonary inflammation ameliorated acute lung injury in neonatal animal models ( 32-34 ). The present research confirmed that miR-490-3p was significantly downregulated in the LPS-induced neonatal ALI rat model.…”
Section: Discussionmentioning
confidence: 99%